Substructural Response Reconstruction in Wavelet Domain - Li, Jun; Law, S. (ASME-AMER SOC MECHANICAL ENG, 2011)
An approach for structural response reconstruction in a substructure using the unit impulse response function in the wavelet domain is presented. The forces at the interface degrees-of-freedom are taken as input excitations on the substructure. The response reconstruction is conducted by transforming the measured responses into responses at other selected locations. The response reconstruction using the proposed wavelet domain method is then compared with that from an existing frequency domain method. Numerical studies on a seven-story plane frame structure are carried out to investigate the accuracy and effectiveness of the proposed method, and the effects of influencing parameters such as the number of sampled data, sampling rate, sensor numbers, and measurement noise are studied.